2021
DOI: 10.3390/foods10091980
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Impact Damage to Whole Apples Packaged Inside Molded Fiber and Expanded Polystyrene Trays

Abstract: Postharvest damage, leading to loss and waste, continues to be a significant problem in the fresh produce industry. Trays, designed to reduce fruit-to-fruit contact, are utilized by the apple industry to minimize bruising of whole apples. During distribution, packaged apples are subjected to various supply chain hazards, which may lead to bruising damage. Currently, molded fiber (MF) and expanded polystyrene (EPS) trays transport whole apples from the packhouse to the retail outlet. Mechanical shock, by free-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In this case, it increases the possibility of damage to the fruit. Ahmadi et al (2010); Zarifneshat et al (2010); Crisosto (1994); Shafie et al (2017); Dunno et al (2021); Aboud (2006); Pathare and Al‐Dairi (2021) determined in their study that an increase in the impact energy level causes an increase in the number of bruises.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In this case, it increases the possibility of damage to the fruit. Ahmadi et al (2010); Zarifneshat et al (2010); Crisosto (1994); Shafie et al (2017); Dunno et al (2021); Aboud (2006); Pathare and Al‐Dairi (2021) determined in their study that an increase in the impact energy level causes an increase in the number of bruises.…”
Section: Resultsmentioning
confidence: 98%
“…It was found that foam-mesh materials significantly reduced the vibration intensity during transportation and provided a more pronounced protective effect than paper-wrapped packages. Dunno et al (2021) investigated the susceptibility of "Minneiska" (SweeTango ® ) apples packed in Molded Fiber (MF) and Expanded Polystyrene Trays (EPS) to impact bruises. In order to evaluate the protective structure of the selected trays, the free-fall method was applied to the packaged product systems.…”
Section: Introductionmentioning
confidence: 99%
“…Scientists believe that up to 35% of bruises occur during harvesting and transportation [23]. In order to minimize post-harvest losses, proper management, transportation, and storage techniques are needed.…”
Section: Introductionmentioning
confidence: 99%